2016
DOI: 10.1088/2053-1583/3/2/025002
|View full text |Cite
|
Sign up to set email alerts
|

Exfoliated black phosphorus gas sensing properties at room temperature

Abstract: Room temperature gas sensing properties of chemically exfoliated black phosphorus (BP) to oxidizing (NO 2 , CO 2 ) and reducing (NH 3 , H 2 , CO) gases in a dry air carrier have been reported. To study the gas sensing properties of BP, chemically exfoliated BP flakes have been drop casted on Si 3 N 4 substrates provided with Pt comb-type interdigitated electrodes in N 2 atmosphere. Scanning electron microscopy and x-ray photoelectron spectroscopy characterizations show respectively the occurrence of a mixed st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(80 citation statements)
references
References 35 publications
2
78
0
Order By: Relevance
“…Naturally existing lone pairs of phosphor atoms confirm that BP is a promising material for use as a gas sensor . It has also been shown that the charge transfer between physioabsorbed gas molecules and BP can be increased by introducing ripples .…”
Section: Our Visionsmentioning
confidence: 95%
“…Naturally existing lone pairs of phosphor atoms confirm that BP is a promising material for use as a gas sensor . It has also been shown that the charge transfer between physioabsorbed gas molecules and BP can be increased by introducing ripples .…”
Section: Our Visionsmentioning
confidence: 95%
“…66 Due to the lone electron pair on each phosphorus atom in phosphorene, it is also a very promising material for gas sensing applications. 92 Organic molecules such as tetracyano-pquinodimethane (TCNQ) have been predicted to act as acceptors once absorbed onto phosphorene. 93 TCNQ provides shallow states near the valence band, which enhances p-type conductivity.…”
Section: Applications Of Phosphorene Electronic Devices and Sensorsmentioning
confidence: 99%
“…15,16 Several authors have reported theoretical and experimental studies that show phosphorene's interaction with many small molecules, and their effect on its resistance and carrier density capabilities, enables the selective detection and measurement of such molecules. 5,8,[17][18][19][20][21][22][23][24][25][26][27][28][29][30] Recently published reviews associated to advances in the eld of 2D materials for sensing applications, provide a clear picture of the opportunities and challenges offered by phosphorene. [31][32][33][34] One of the main problems in its widespread use for sensing applications is its stability under ambient conditions.…”
Section: Introductionmentioning
confidence: 99%